The fifth beatle ebook The brian epstein story. - Tiwary, Vivek J. (Dark Horse Comics, LLC., 2023)
"Heartbreaking, exhilarating and unexpected . . . A complete triumph."—The Hollywood Reporter "10/10. A masterpiece . . . Brilliant in every aspect."—IGN's Best Original Graphic Novel, 2013The Fifth Beatle brings to life the true story of visionary Beatles manager Brian Epstein—the man who launched the Beatles to worldwide stardom.This 10th Anniversary edition of the critically acclaimed, award-winning international bestseller features a new cover, an accompanying musical soundtrack/playlist curated by writer Vivek J. Tiwary, a new introduction by legendary music manager Kelly Curtis (Pearl Jam), and an expanded sketchbook section.A visionary artist manager, Brian Epstein engineered Beatlemania—guiding the Beatles from basement gigs to unprecedented international stardom while wrestling with personal demons and the trappings of massive ambition and success. An award-winning, uplifting and inspiring human story about chasing your dreams, The Fifth Beatle also reveals an important, unsung chapter in the Beatles' history.Whether you're discovering the Brian Epstein story for the first time or an old fan revisiting this groundbreaking graphic novel, now a part of the Rock and Roll Hall of Fame Library and Archives Permanent Collection, a splendid time is guaranteed for all.